2013
DOI: 10.1371/journal.pone.0059923
|View full text |Cite
|
Sign up to set email alerts
|

Parental Weight Perceptions: A Cause for Concern in the Prevention and Management of Childhood Obesity in the United Arab Emirates

Abstract: Parental participation is a key factor in the prevention and management of childhood obesity, thus parental recognition of weight problems is essential. We estimated parental perceptions and their determinants in the Emirati population. We invited 1541 students (grade 1–12; 50% boys) and their parents, but only 1440 (6–19 years) and their parents consented. Of these, 945 Emirati nationals provided data for analysis. Anthropometric and demographic variables were measured by standard methods. CDC BMI percentile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
3
36
0
1
Order By: Relevance
“…10 Other studies from different parts in the world show similar results. In UK Jeffery N et al in 2014 showed that Mothers often do not realize when their child is overweight and this was a barrier for successful weight reduction programs as the parents will not engage in such programs while they remain ignorant of the problem.…”
Section: Discussionsupporting
confidence: 54%
“…10 Other studies from different parts in the world show similar results. In UK Jeffery N et al in 2014 showed that Mothers often do not realize when their child is overweight and this was a barrier for successful weight reduction programs as the parents will not engage in such programs while they remain ignorant of the problem.…”
Section: Discussionsupporting
confidence: 54%
“…The adjusted analyses confirmed they were twice as likely to underestimate their child's weight if they were overweight themselves. fathers than in mothers (3) as well as those with lower educational levels (3) or lower family income (11). The influence of the parents' own weight on the misperception of the children's weight was examined in two studies that included children who were up to five years of age (3,9) and in another investigation with participants aged two to 19 years (12).…”
Section: Key Notesmentioning
confidence: 99%
“…Little is known about the reasons that could explain the low capacity of parents to recognise children being overweight and even less is known about this in children during adolescence. In addition to variations according to the gender and age of children and adolescents , some authors found that misperceptions were more common in fathers than in mothers as well as those with lower educational levels or lower family income . The influence of the parents' own weight on the misperception of the children's weight was examined in two studies that included children who were up to five years of age and in another investigation with participants aged two to 19 years .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to risk perception it might be important to consider whether parents evaluate their children's weight status correctly in the first place. Research showed that between 50-80% of parents of overweight or obese children underestimate their children's weight status (Aljunaibi, Abdulle, & Nagelkerke, 2013;Etelson, Brand, Patrick, & Shirali, 2003;Hudson, McGloin, & McConnon, 2012;Lim & Wang, 2013;Lundahl, Kidwell, & Nelson, 2014). This misperception might hinder parents to take appropriate measures to ameliorate weight status and to prevent potential health problems associated with overweight.…”
Section: Introductionmentioning
confidence: 99%